Sentence length and structure in the modern spoken Lithuanian - Balčiūnienė, Ingrida; Kamandulytė-Merfeldienė, Laura (Lietuvių kalba, 2016)
Syntactic features of spoken Lithuanian still lack of studies due to insufficient data basis and limited technologies and research methodologies. During the last years, the Corpus of Spoken Lithuanian (developed at Vytautas Magnus University) has been syntactically annotated and this has enabled for complex automatized syntactic analysis. In this paper, one of the first such studies is presented and its results are discussed. After a comparative analysis of different data samples (e.g., public vs. private speech; monologues vs. dialogues; spontaneous vs. prepared speech), the following can be stated. In the public speech (and, particularly, in the academic speeches), the mean length of utterances are much higher and the syntactic structures are rather simpler than those in the private conversations. Some syntactic features (e.g., the mean length of utterance) of the spoken Lithuanian might partially correlate to those typical for some genres of the written Lithuanian; however, some specific of an oral speech influences a frequency of some particular types of utterances (e.g. asyndetic sentences). The results still have to be verified by the means of statistical analysis, but preliminary two-side correlation between the sentence length and structure of the Modern Spoken Lithuanian might be emphasized.
Keywords: syntactic analysis; spoken Lithuanian; sentence length